Tirzepatide - A Revolution in Obesity Treatment? - Jaroń, Aleksandra; Jastrzębska, Katarzyna; Wojciechowska, Klara; Turek, Monika; Chaberska, Iwona; Feruś, Aleksandra; Lipska, Julia; Piątkowska, Karolina (Quality in Sport, 2024)
Introduction and aim of study: Obesity is a chronic disease associated with numerous health complications, and the number of patients is steadily increasing. Pharmacological methods for treating obesity are becoming increasingly popular. This paper aims to review publications concerning the efficacy and safety profile of tirzepatide, the only dual agonist of two human incretin receptors: GLP-1 and GIP, and the latest drug used for this indication. Materials and Methods: Two databases, Pubmed and Medline, were searched using the terms "tirzepatide" and "obesity". Results: Studies indicate significant and sustained weight reduction in obese patients during tirzepatide use as a complement to lifestyle changes. The greatest average weight reduction (20.9%) was observed in patients without concomitant type II diabetes using a 15 mg dose of tirzepatide. Following an initial intensive lifestyle change, obese patients can expect further clinically significant weight loss with the addition of tirzepatide to their treatment. However, discontinuing tirzepatide after initial weight reduction is associated with significant weight regain. Furthermore, studies show that tirzepatide use results in the greatest weight reduction among available market preparations. The drug also has other health benefits, but its use is associated with numerous adverse effects, including severe ones. Conclusions: Pharmacotherapy can facilitate the process of lifestyle modification but remains a supportive treatment. During obesity treatment with tirzepatide, it is important to consider the actual health benefits and its effectiveness in weight reduction, keeping in mind its safety profile and potential risks.